Govor o cenzuri zahteva natančnost glede njenega domnevnega predmeta - Lambrichs, Louise L. (Primerjalna književnost, 2008)
In March 2006, Peter Handke went to Milošević''s funeral, where he gave a speech saying he still did not know the truth about Yugoslavia''s war and Milošević''s responsibility. This event gave rise to a scandal or "affair", called "L''affaire Handke", starting with a petition signed by Elfriede Jelinek and other artists, denouncing the "censorship" Handke was a victim of. Reconstructing this affair, I shall analyze various questions: was it relevant to say that Handke was a victim of "censorship"? What was the position of the various people that came to Handke''s defence? What was the position of those that criticized him? Are they talking about the same thing? Obviously, the answers to these questions depend on the object considered to be the supposed object of censure: the writer himself (as free to say anything he wants), or the thing he is talking about - a very cruel war and genocide in Bosnia.
Keywords: Handke, Peter, 1942-; literatura in cenzura; avstrijska književnost; politični angažma; svoboda govora